Development of self-compacting mortar incorporating calcium carbonate and waste garnet: Workability, strength, and fire durability assessment - Chatveera, Burachat; Ejaz, Ali; Chintanapakdee, Chatpan; Saingam, Panumas; Hussain, Qudeer; Sua-iam, Gritsada (My University, 2026)
The excessive consumption of natural sand and cement in mortar production raises environmental concerns, underscoring the need for sustainable alternatives. While the separate use of cementitious and fine aggregate substitutes has been studied, their combined effects in self-compacting mortar (SCM) remain underexplored. This study addresses this gap by investigating SCM mixes incorporating calcium carbonate (CaCO₃) as a partial cement substitute (0–20%) and waste garnet (0–100%) as a fine aggregate replacement. A total of 18 mixes were evaluated for their fresh properties, mechanical performance, durability, and residual properties after elevated-temperature exposure. The results showed that the mix with 10% CaCO₃ and 60% waste garnet exhibited the best overall performance, achieving approximately 66 MPa compressive strength and 8.1 MPa flexural strength at 90 days, representing up to a 15% improvement over the control. Water absorption was reduced to 2.42% at 90 days, while improved resistance under acidic conditions was observed, with only 7.71% mass loss after 180 days of exposure to 5% H₂SO₄ solution. Furthermore, the optimized mix retained over 65% of its compressive strength after exposure to 600 °C, indicating good residual mechanical performance at elevated temperatures. Microstructural analysis revealed a dense and cohesive matrix with a refined pore structure. These findings suggest that the combined use of CaCO₃ and waste garnet can provide a potentially eco-efficient approach for producing high-performance SCM. The improved workability, strength, and durability indicate potential suitability for applications such as repair mortars and precast elements, where both flowability and long-term performance are required.
Keywords: Calcium carbonate; Fire durability; Self-compacting mortar; Waste garnet; Waste valorization